State of the art review of the existing soft computing based approaches to trust and reputation computation - Hussain, Farookh; Chang, Elizabeth; Hussain, Omar (IEEE, 2007)
In this paper we present a state of the art review of PageRanktrade based approaches for trust and reputation computation. We divide the approaches that make use of PageRanktrade method for trust and reputation computation, into six different classes. Each of the six classes is discussed in this paper.